Oral Cavity and Pharynx Cancer Incidence Trends by Subsite in the United States: Changing Gender Patterns. (17th April 2012) - Brown, Linda Morris; Check, David P.; Devesa, Susan S.
Abstract : Objective . To evaluate oral cavity and pharynx cancer (OCPC) patterns by gender. Methods . We used Surveillance, Epidemiology, and End Results program data for 71, 446 cases diagnosed during 1975–2008 to classify OCPC by anatomic subsite as potentially HPV-related or not, with oral tongue cancer considered a separate category. Results . Total OCPC rates among men were 2–4 times those among women. Among whites, total OCPC rates rose in the younger age groups due to substantial increases in successive birth cohorts for HPV-related cancers, more rapid among men than women, and oral tongue cancers, more rapid among women than men. Among blacks, total OCPC rates declined among cohorts born since 1930 reflecting the strong downward trends for HPV-unrelated sites. Among Hispanics and Asians, HPV-unrelated cancer rates generally declined, and oral tongue cancer rates appeared to be converging among young men and women. Conclusions . Decreases in total OCPC incidence reflect reductions in smoking and alcohol drinking. Rising HPV-related cancers among white men may reflect changing sexual practices. Reasons for the increasing young oral tongue cancer rates are unknown, but the narrowing of the gender differences provides a clue.